Twelve Plays for Young People - Segun, Mabel (Nigeria, 2006)
Readers' Theatre is an effective and exciting means of giving young people practice in using language in a natural way without having to memorize lines. Some of the plays in this book are based on folktales while others are about Nigerian historical, legendary and fictional heroes and heroines who have had to face certain challenges...
Keywords: Drama; Juvenile Fiction